Measuring the Research Competency Needs of University Student-Researchers: Content Validity and Reliability of a Survey Tool - Pecson, Ryan R.; Jr., Romeo T. Quintos, (PT FORMOSA CENDEKIA GLOBAL, 2025)
Measuring the research competency needs of university student-researchers ensures a holistic and responsive approach to addressing their research dilemmas, thereby ensuring the maximum utility of any research projects for learning progress and development. With this intention, the present study proposes a 32-item survey tool to assess research competency needs of student-researchers across eight domains. Using the instrument development research as the design, three experts validated the survey tool, while 30 university students participated in a dry run to establish the instrument’s reliability. The survey tool is subjected to validity testing using Kappa Statistics and reliability testing using Cronbach’s Alpha. Results indicate that the developed survey tool is highly valid (I-CVI=1.00) and highly reliable (α=0.963), making it suitable to assess the research competency needs.